Creating a sustainable quality management system in assisted reproductive technologies - Mitko Ivanovski (Journal of Contemporary Economic and Business Issues, 2015)
Assisted reproductive technology (ART) programs are complex organizations requiring the integration of multiple disciplines. ISO 9001:2008 is a quality management system that is readily adaptable to an ART program. A quality ART program sets quality objectives and monitors their progress. ISO provides a sense of transparency within the organization and clearer understanding of how service is provided to patients. Most importantly, ISO provides the framework to allow for continual improvement. Thus, the purpose of this study is to establish a framework by which to approach the issue of quality management system in ART, delineate the various components of quality that exist in health care, and explore how these elements affect one another. The process management philosophy in ART begins its focus on the customer/patient and their requirements; everything to do with quality starts and ends with the customer/ patient. What the customer/patient wants, needs and expects becomes the input to the quality management system. This input then feeds into the service planning process and finally into requirements for service delivery. Management responsibility (leadership), resource management (people, facilities and equipment), product realization (process) and measurement analysis and improvement (improvement for the customer/patient satisfaction) describe what practices must do to deliver quality services. To the customers, competitors and the outside world, a clinic/practice's business strategy is communicated through its marketing message, strategic partnerships and development of mutually beneficial supplier relationships. In order to assure high quality and continual improvement, it is recommended that all ART centers striving for excellence should consider a Quality Management system.
Keywords: I11; J13; 330; assisted reproductive technologies; quality management system; ISO standards